(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The goal of this study is to look at the recently announced plans for financial inclusion, with a focus on how they might help groups with low incomes. Design, methodology, and approach: This study included microfinance and micro insurance programmes to learn about their effects on a sample of 100 people from all walks of life in the Agra district, India. The results show that people have a good idea of what has been done and how much better off they are as a result of the various financial inclusion programmes. The populace is making use of microfinance and micro insurance to engage in agricultural pursuits, animal husbandry, and the establishment of their own businesses. All types of people support the GOI’s plan to use MF and MI to revive India’s sagging economy. This study’s novel findings will aid in the spread of banking services across economically and socially disadvantaged communities, thus fostering financial inclusion and inclusive growth. Increased access to banking by rural residents, spurred by lower fees, will hasten the spread of inclusive funding and development. As this study shows, financial institutions should work to create synergies with technology providers in order to reach the general public and help as many poor people as possible. This would also help them deal with low-value, high-volume transactions in an efficient and effective way.